2017
DOI: 10.4236/ajac.2017.86032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Standards and Interfering Compounds in the Determination of Phenolics by Folin-Ciocalteu Assay Method for Effective Bioprocessing of Biomass

Abstract: Folin Ciocalteu (F-C) assay is the most widely used and convenient method to determine the total phenolics content in foods, herbs, and other plant extracts. Different phenolics standards such as gallic acid, ferulic acid, chlorogenic acid, catechol, and vanillic acid have been used for calibration curves in this assay method. Comparison of these standards, in single or combination of two or more, for more accurate determination of phenolics has not been reported so far. This study tested five single phenolics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 30 publications
2
48
0
13
Order By: Relevance
“…Soluble and bound phenolic contents in other samples were low, ranging from 0.1 to 2 g/100 g dm and from 0.3 to 3 g/100 g dm, respectively). These values should be interpreted with care, as it is well known that some compounds can interfere with this Folin‐Ciocalteu method, such as ascorbic acid and some organic acids (Bastola et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Soluble and bound phenolic contents in other samples were low, ranging from 0.1 to 2 g/100 g dm and from 0.3 to 3 g/100 g dm, respectively). These values should be interpreted with care, as it is well known that some compounds can interfere with this Folin‐Ciocalteu method, such as ascorbic acid and some organic acids (Bastola et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…It is not specific for TP determination and is prone to interfering compounds presented in the sample leading to biased estimation. Reducing sugars which are present in high concentration in dates and ascorbic acid, which is present in substantial level at some developmental stages, are examples of these interfering compounds [20]. Most of the published studies reporting TP in dates did not adequately address this issue.…”
Section: The Issue Of Large Variability Of Total Phenolic Contentmentioning
confidence: 99%
“…Ciocalteu reagent is not specific to phenolic compounds that some substances such as amino acids, simple sugars, some organic acids, and vitamins show reactivity toward the reagent(Everette et al, 2010). However, in another study it was shown that HMF did not interferein the determination of phenolic compounds(Bastola, Guragain, Bhadriraju, & Vadlani, 2017). Thus,…”
mentioning
confidence: 97%